2017
DOI: 10.1111/anu.12547
|View full text |Cite
|
Sign up to set email alerts
|

Different preference is modulated by the feeding stimulants supplementation in different Chinese soft-shelled turtle (Pelodiscus sinensis ) basic diets

Abstract: Five 2-week feeding trials were conducted to investigate five stimulants on P. sinensis.Two isonitrogenous and isoenergetic diets were formulated, one contained 600 g kgfishmeal (FM diet) and the other contained 420 g kg -1 fishmeal and 225 g kg -1 animal protein blend (APB diet), and each tested one stimulant with four levels. The feeding stimulant candidates were betaine, 2-carboxy-ethyl dimethyl sulphonium bromide (DMPT), inosine-5′-monophosphate (IMP), taurine and squid extract. In the experiment on each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…In the present study, turtles fed diets included squid paste presented lower peak mRNA level of CCK and CCK1R than that in other groups. It might be accounted for the improved activities of the digestive enzyme in the RPS group (Sun et al, 2018a;Sun et al, 2018b). Similar results were also found in grass carp (Liu et al, 2014;Huang et al, 2019).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In the present study, turtles fed diets included squid paste presented lower peak mRNA level of CCK and CCK1R than that in other groups. It might be accounted for the improved activities of the digestive enzyme in the RPS group (Sun et al, 2018a;Sun et al, 2018b). Similar results were also found in grass carp (Liu et al, 2014;Huang et al, 2019).…”
Section: Discussionsupporting
confidence: 80%
“…RPS diet was different from the RP diet by the inclusion of 1% squid paste. This concentration of squid paste was determined by the optimal dietary preference of Pelodiscus sinensis (Sun et al, 2018a;Sun et al, 2018b). To maintain the consistencies of essential amino acid profiles in the experimental diets, microcapsule lysine was supplemented according to the essential amino acid profiles of the CT diet.…”
Section: Experimental Feedsmentioning
confidence: 99%
See 1 more Smart Citation
“…taste and smell) to locate food (Velez et al, ). Reports presented that volatile organic acids, sugars, amino acids and sulphur‐containing organic compounds had significant influence in the feeding attraction activity of aquatic animals (Hara, ; Harada & Matsuda, ; Harada et al, ; Pan, Xian, Kou, Wang, & Miao, ; Sun et al, ; Xue & Cui, ; Zhang et al, ). In this study, medicinal plant garlic powder showed significant feeding attraction activity for Japanese seabass.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the molecular mechanisms of growth regulation and the genetic basis of growth variation may contribute to the genetic improvement of P. sinensis . Nowadays, many studies of P. sinensis in the fields of nutrition (Cheng, Huang, Wang, & Guanghong, 2017; Ji, Liu, Li, & Yang, 2017; Sun et al, 2018), immune (Lyu et al, 2020), and sex control (Cai et al, 2016; Sun et al, 2017) have been reported, while the molecular mechanisms involved in its growth are poorly understood.…”
Section: Introductionmentioning
confidence: 99%